KEPEMILIKAN TERKONSENTRASI DAN KEBIJAKAN PEMBAYARAN DIVIDEN PADA PERUSAHAAN SEKTOR PERBANKAN DI PT BURSA EFEK INDONESIA - taufik .; Marlina Widiyanti (Program Studi Magister Manajemen FE Unsri, 2014)
This research aimed to determine the effect of concentred ownership, firm size, leverage and profitability to dividend payout policy of banking firms sector on the Indonesian stock exchange period of 2005 – 2012. Purposive sampling was used in this research. Off 34 banking firms, only 5 banking firms were carried out as samples. Multiple regression, t test and F test hypotheses were implemented to see the influence of concentred ownership, firm size, leverage and profitability to dividend payout policy. The result of t test showed that only leverage had no influence to dividend payout policy while concentred ownership, firm size and profitability had positive and significant effect to dividend payout policy. The result of F test indicated that concentred ownership, firm size, leverage and profitability had positive and significant influence to dividend payout policy. For furthet research, it is recommended to include other related variables.